2021
DOI: 10.1093/bjsw/bcab248
|View full text |Cite
|
Sign up to set email alerts
|

Recognising children’s involvement in child and family therapy sessions: A microanalysis of audiovisual recordings of actual practice

Abstract: Children’s right to involvement in practices that address their well-being is frequently highlighted, yet how children exercise involvement in face-to-face encounters has remained fairly unknown. To fulfil our aim of identifying, describing and defining children’s involvement, we conducted an inductive microanalysis of face-to-face dialogue on audiovisual recordings of naturally occurring therapy sessions with children attending social services departments and mental health clinics. The resulting operationalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…From their perspective, children's involvement is more complex than single acts and consists of behavioral, cognitive, and emotional elements. Similar to Edman et al (2022), Morris et al (2016) also argued that children's involvement in child and family therapies is multifaceted and may extend beyond the therapeutic setting.…”
Section: Children's In-session Involvement In Child and Family Therapiesmentioning
confidence: 97%
See 3 more Smart Citations
“…From their perspective, children's involvement is more complex than single acts and consists of behavioral, cognitive, and emotional elements. Similar to Edman et al (2022), Morris et al (2016) also argued that children's involvement in child and family therapies is multifaceted and may extend beyond the therapeutic setting.…”
Section: Children's In-session Involvement In Child and Family Therapiesmentioning
confidence: 97%
“…While emphasizing that involvement is more complex than any single act, Morris et al (2016), like B. C. Chu and Kendall (2004) and Cederborg (1997), approached children's involvement as measurable and concluded that a greater degree of children's involvement is desirable. In contrast, Edman et al (2022) proposed that children's involvement in child and family therapies is inevitable and identified six nonmethod-specific dimensions to children's involvement: participatory, directive, positional, emotional, agentive, and narrative. In line with the other scholars (e.g., Ovenstad et al, 2023;Tambuyzer et al, 2014), Edman et al (2022) argued that children's involvement behaviors are not innately positive and that practitioners need to be mindful of the implications that the various dimensions to children's involvement may bring.…”
Section: Children's In-session Involvement In Child and Family Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Audiovisual recordings have been utilized in research studies in other disciplines such as music, history, education, and the social sciences (Duan et al, 2019; Maltese et al, 2016; Martin et al, 2021; Pallotti et al, 2020). In health care settings, audiovisual recordings are often used for training purposes or for observing staff workflow (DiGioia et al, 2012; Edman et al, 2022; MacLean et al, 2019; Van Gelderen et al, 2016), or more recently, to conduct research utilizing video or telehealth platforms with families (Bogulski et al, in press; Holuszko et al, 2022; Lobe et al, 2020). Often, audio-only recordings or observations are used to study interactions between nurses and families, particularly in pediatrics (Choe et al, 2021; Walter et al, 2019).…”
Section: Prior Use and Significance Of Audiovisual Recordingmentioning
confidence: 99%